Accumulation effect of soil aggregate organic carbon in mixed forest in open-pit coal mine - Xiaoping ZHANG; Mingchao LI; Yinli BI; Xin LI (Meitan kexue jishu)
Mining activities result in the depletion of soil nutrients and carbon reservoirs. A pressing need exists to examine soil nutrient status, particularly the recovery of organic matter following prolonged revegetation in open pit mines. In a nearly two-decade-long reclamation effort at the northern dump of Heidaigou Open-pit Coal Mine, both pure pine forests and mixed pine forests were chosen. A thorough and systematic investigation into aggregate stability and the recovery of associated carbon pools in the reclaimed area was undertaken. The study findings revealed that: Soil aggregate stability was superior in pine mixed forests compared to pure pine forests. In the 0-10 cm surface soil, the highest aggregate stability occurred in pine, mountain, apricot, and poplar mixed forest, followed by pine and poplar mixed forest. In the 0−20 cm and 20−30 cm subsurface soils, poplar and Chinese pine mixed forests exhibited larger average mass diameter and geometric mean diameter, with the smallest fractal dimension. In comparison to the other three vegetation combinations, the overall stability of soil structure was superior. Chinese pine mixed forests displayed higher soil organic carbon content than Chinese pine pure forests. The mixed forest elevated the proportion of inert organic carbon, enhancing soil carbon pool stability. In the same soil layer, the content of organic carbon and its components in each particle size of soil aggregates was generally higher in Chinese pine mixed forests than in Chinese pine pure forests, gradually decreasing with soil depth. Changes in oxidizable organic carbon and inert organic carbon in aggregates of each particle size mirrored those of organic carbon, exhibiting an inverted V-shaped distribution. Soil organic carbon and easily oxidizable organic carbon content in aggregates of 0.25−2 mm size were significantly higher than in other size groups. Influential factors on total organic carbon include soil total nitrogen content and mean mass diameter (MWD); those affecting easily oxidizable organic carbon content are total nitrogen content and pH value, and the factors influencing particulate organic carbon content include soil total nitrogen content, available potassium content, and mean mass diameter. Soil organic carbon and active carbon contents were significantly positively correlated with diversity index, vegetation biomass, and litter biomass. Overall, the study results demonstrate that the restoration impact of the mixed pine forest in the Heidaigou open-pit mine dump surpasses that of the pure Chinese pine forest. Notably, the mixed plantation of “Chinese pine + apricot + poplar” exhibits the most effective recovery of soil organic carbon.